2014
DOI: 10.1097/ccm.0b013e3182a26ff3
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Perceived Benefits of a Framework for Physician-Parent Follow-Up Meetings After a Child’s Death in the PICU*

Abstract: Objective To evaluate the feasibility and perceived benefits of conducting physician-parent follow-up meetings after a child’s death in the PICU according to a framework developed by the Collaborative Pediatric Critical Care Research Network (CPCCRN). Design Prospective observational study. Setting Seven CPCCRN affiliated children’s hospitals. Subjects Critical care attending physicians, bereaved parents, and meeting guests (i.e., parent support persons, other health professionals). Interventions: Physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(45 citation statements)
references
References 25 publications
1
44
0
Order By: Relevance
“…A variety of practices are used when there is follow‐up, including making phone calls; sending cards; attending funerals; providing information and resources; connecting parents with other bereaved parents; acknowledging birthdays, holidays, and anniversaries; visiting the family; holding family meetings; and organizing memorial services . Qualitative studies have found that phone calls and family meetings after the child's death are beneficial, helping parents feel like their child is remembered, facilitating meaning‐making, responding to unanswered questions about their child's care, reassuring them they did everything they could, and providing a sense of closure . Of note, some follow‐up efforts have been perceived as inadequate, suggesting the importance of training staff.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of practices are used when there is follow‐up, including making phone calls; sending cards; attending funerals; providing information and resources; connecting parents with other bereaved parents; acknowledging birthdays, holidays, and anniversaries; visiting the family; holding family meetings; and organizing memorial services . Qualitative studies have found that phone calls and family meetings after the child's death are beneficial, helping parents feel like their child is remembered, facilitating meaning‐making, responding to unanswered questions about their child's care, reassuring them they did everything they could, and providing a sense of closure . Of note, some follow‐up efforts have been perceived as inadequate, suggesting the importance of training staff.…”
Section: Resultsmentioning
confidence: 99%
“…Despite a growing recognition that bereavement care is inherent to good clinical care, physicians often receive little training on how to compassionately and professionally communicate with families after a loss. 14,15,18,21,29,30 Many physicians learn about bereavement care from mentors or through a ''trial and error'' approach rather than through dedicated training. 18 Most pediatric oncology fellows do not receive specific education in provision of bereavement care as this is not part of the required curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the original study was to assess the feasibility of conducting bereavement meetings as described by the CPCCRN framework (Eggly et al, 2011). Detailed information about recruitment and other procedures for the original study is provided elsewhere (Meert et al, 2014). The CPCCRN is a multicenter research network consisting of seven U.S. tertiary care academic pediatric centers and a data coordinating center.…”
Section: Methodsmentioning
confidence: 99%